Sedimentological data sets from the prehistoric site of Ajor Pazi (northern Iran) - Busch, Robert; Bernbeck, Reinhard; Hessari, Morteza; Kirsten, Fabian; Lüthgens, Christopher; Pollock, Susan; Rol, Nolwen; Schütt, Brigitta (PANGAEA, 2024)
During a rescue excavation in 2018, 136 sedimentary bulk samples were collected from sediment cross-sections at the prehistoric site of Ajor Pazi (northern Iran). This study aimed to understand the prehistoric human-environmental interactions in an active fluvial fan setting. Using radiocarbon and luminescence-dated sedimentary cross sections, we applied multivariate statistics to sedimentological characteristics (magnetic susceptibility, grain size, remission, total organic and total inorganic carbon, and X-ray fluorescence) interpreted in terms of depositional facies. Based on numerical and material dating and facies interpretation, the first settlement activities must have occurred between 6.4 - 5.6 ka cal. BP (4.4 - 3.6 ka cal. BCE), which archaeologically falls into the Transitional Chalcolithic II period.
Keywords: Alluvial fan; Carbon; Iran; Magnetic susceptibility; mid-holocene; pXRF; sediment colour; sediment profiles